A simple nonlinear PD control for faster and high-precision positioning of servomechanisms with actuator saturation. (15th April 2019) - Zheng, Chunhong; Su, Yuxin; Mercorelli, Paolo
Highlights: Propose a simple but effective nonlinear proportional-derivative (PD) control faster and high-precision positioning of servomechanisms subject to actuator saturation. Prove global asymptotic stability. Demonstrate the effectiveness and improved performance through numerical simulations and real experiments. The proposed control has simple intuitive structure with high computational efficiency and does not involve modelling parameter. The proposed control has the ability to ensure that actuator constraint is not breached, and thus it completely avoids the performance degradation from excessive torque. Abstract: This paper investigates the problem of high performance motion control for servomechanisms subject to actuator saturation. A very simple but quite effective nonlinear proportional-derivative (PD) control is proposed for faster and high-precision positioning of such systems. The particular reasoning behind our concern on nonlinear PD (NPD) control is that most of practical servomechanisms so far are still controlled by classic proportional-integral-derivative (PID)/PD or nonlinear PID (NPID)/NPD algorithms and these controls do not explicitly take into account actuator constraint. Lyapunov's direct method is employed to prove global asymptotic positioning stability. The appealing advantages of the proposed control are that it has simple intuitive structure with high computational efficiency and does not involve modelling parameter. An additive feature is that the proposed control has the ability to ensure that actuator constraint is not breached, and thus it completely avoids the instability and degraded or unpredictable motion and thermal or mechanical failure from excessive torque. Simulations and experimental results demonstrate that the proposed approach offers a comparable result over the existing model-dependent nonlinear controls and a much improved performance over the commonly-used model-independent linear PD control for servomechanisms with actuator constraint.